2018
DOI: 10.1155/2018/9610812
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation (tDCS) Paired with Occupation-Centered Bimanual Training in Children with Unilateral Cerebral Palsy: A Preliminary Study

Abstract: Objective We investigated the preliminary efficacy of cathodal transcranial direct current stimulation (tDCS) combined with bimanual training in children and young adults with unilateral cerebral palsy based on the principle of exaggerated interhemispheric inhibition (IHI). Methods Eight participants with corticospinal tract (CST) connectivity from the lesioned hemisphere participated in an open-label study of 10 sessions of cathodal tDCS to the nonlesioned hemisphere (20 minutes) concurrently with bimanual, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…Our rationale was that the activity of inhibitory circuits within contralesional M1 may also increase following cathodal tDCS, as demonstrated in a prior study investigating rehabilitation and tDCS in adults with stroke (Goodwill et al, 2016). Using a similar assessment of CSP duration to Rich et al (2018), we observed increased CSP duration in three of eight individuals in the Active+CIMT group and zero of seven in the Sham+CIMT. Still, the changes in CSP duration were highly variable and were not statistically significant at the group level.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our rationale was that the activity of inhibitory circuits within contralesional M1 may also increase following cathodal tDCS, as demonstrated in a prior study investigating rehabilitation and tDCS in adults with stroke (Goodwill et al, 2016). Using a similar assessment of CSP duration to Rich et al (2018), we observed increased CSP duration in three of eight individuals in the Active+CIMT group and zero of seven in the Sham+CIMT. Still, the changes in CSP duration were highly variable and were not statistically significant at the group level.…”
Section: Discussionsupporting
confidence: 74%
“…Combined tDCS and intensive motor training interventions have recently been investigated in children with UCP, with results showing some positive changes in neurophysiologic responses, motor function, and activities of daily living skills (Grecco et al, 2014; Collange Grecco et al, 2015; Kirton et al, 2017; Gillick et al, 2018b; Rich et al, 2018). While these initial studies have focused on establishing the safety of these combined tDCS and rehabilitation interventions and their effects on behavioral, little is known regarding their on influence corticospinal excitability in children with UCP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to treatment of brain diseases associated with pathological enhancement of cortical activity or excitability via cathodal tDCS, some studies have reported that ctDCS applied over an epileptogenic focus reduces epileptic EEG abnormalities [11,12] and seizure frequency in epilepsy [13]. Clinical studies moreover showed that cathodal tDCS over the contralesional M1 combined with motor training rebalances bi-hemispheric activity and facilitates motor performance in stroke patients [14,15] and in children with cerebral palsy [16,17]. Furuya et al describe that ctDCS applied over the affected motor cortex in musicians cramp, combined with anodal tDCS over the contralateral motor cortex and bimanual finger movements, reduces dystonic symptoms in these patients, most probably due to a reduction of pathologically enhanced activity of the affected M1 [18].…”
Section: Introductionmentioning
confidence: 99%